Graffiti and gender: a sociolinguistic study of wall writings in selected Pakistani higher learning institutions - Khosa, Durdana; Ramakrishna, Rita A. R. (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2023)
As the most widespread and strongly prohibited activity in Pakistani educational institutions, graffiti writings are the subject of this paper. The article explores graffiti as a gendered activity. The study investigates gender variations in the frequency, types and themes used in the writings. This is done to obtain a comprehensive understanding of gender roles and stereotypes in Pakistan in light of Lakoff's (1975) framework on gender variations in language. Using a qualitative approach, the paper analyses graffiti texts collected from two same-sex colleges in Quetta, the capital of Balochistan. To substantiate the findings from the graffiti texts, semi-structured interviews with students from the same institutions are also conducted. The findings indicate significant variations in how men and women write graffiti. Women outnumber men as graffiti writers, and they tend to use more expletives than men. The primary subjects of male graffiti are politics and sex, whereas female graffiti centres on poetry, romance, songs and slurs. The analysis reveals that while some long-held gender stereotypes proposed by Lakoff (1975) are still widely accepted, there is also some defiance of these norms on the part of men and women alike, indicating a subtle but significant shift in gender roles in Pakistan.